2015
DOI: 10.14348/molcells.2015.2340
|View full text |Cite
|
Sign up to set email alerts
|

Obatoclax Regulates the Proliferation and Fusion of Osteoclast Precursors through the Inhibition of ERK Activation by RANKL

Abstract: Obatoclax, a pan-Bcl2 inhibitor, shows antitumor activities in various solid malignancies. Bcl2-deficient mice have shown the importance of Bcl2 in osteoclasts, as the bone mass of the mice was increased by the induced apoptosis of osteoclasts. Despite the importance of Bcl2, the effects of obatoclax on the proliferation and differentiation of osteoclast precursors have not been studied extensively. Here, we describe the anti-proliferative effects of obatoclax on osteoclast precursors and its negative role on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Although the dramatic decrease of osteoclast fusion in the presence of ERK1 siRNA could be recovered by the collagenase inhibitor, additional ERK2 siRNA completely abrogated the Ro compound-dependent increase of osteoclast size. Previous reports indicated that the inhibition of ERK pathway by the treatment of osteoclast precursors with a MEK inhibitor (U0126 or PD98059) significantly suppressed the expression of Dcstamp [39,40]. Thus, potential mechanisms behind the ERK pathway-dependent enhancement of osteoclast fusion by Ro 32-3555 in current study might involve Dcstamp, considering the suggested pivotal role during the fusion of osteoclasts [9,35,40].…”
Section: Discussionsupporting
confidence: 48%
“…Although the dramatic decrease of osteoclast fusion in the presence of ERK1 siRNA could be recovered by the collagenase inhibitor, additional ERK2 siRNA completely abrogated the Ro compound-dependent increase of osteoclast size. Previous reports indicated that the inhibition of ERK pathway by the treatment of osteoclast precursors with a MEK inhibitor (U0126 or PD98059) significantly suppressed the expression of Dcstamp [39,40]. Thus, potential mechanisms behind the ERK pathway-dependent enhancement of osteoclast fusion by Ro 32-3555 in current study might involve Dcstamp, considering the suggested pivotal role during the fusion of osteoclasts [9,35,40].…”
Section: Discussionsupporting
confidence: 48%
“…They demonstrated that ERK1 positively regulated osteoclastogenesis, and that its disruption decreased multinucleated osteoclast formation from bone marrow mononuclear cells. A later report by Oh et al demonstrated that blockage of ERK1/2 by an ERK inhibitor significantly inhibited the expression of DC-STAMP and Atp6v0s2, and completely eliminated the formation of large, multinucleated osteoclasts [ 40 ]. In addition, two studies have shown the reciprocal regulation of endogenous and exogenous collagenases on DC-STAMP through the MAPK cascade [ 41 , 42 ].…”
Section: Dc-stampmentioning
confidence: 99%
“…As previously reported, psoralen stimulates hFOB1.19 cell proliferation through activation of MAPK/ERK signaling (20). In osteoclasts, it is well established that the activation of MAPK/ERK signaling plays a key role in receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast differentiation (20, 21). Meanwhile, in osteoblasts, studies have demonstrated that the activation of ERK is required for osteogenic mesenchymal stem cell differentiation and skeletal development (22, 23).…”
mentioning
confidence: 99%